Kartel dan Tarif Tiket Perusahaan Penerbangan Terhadap Persaingan Usaha Penerbangan di Indonesia - Mustika Sari; Euis Saribanon; Abdul Ghafar (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2020)
The purpose of the study is to determine whether there is a direct and indirect influence between cartels and ticket tariffs of airlines business competition in Indonesia or not. The problems in this study were due to the high ticket price and public’ indication and suspicions of domestic airlines cartels practicing. The method used in this research was path analysis, to determine the direct and indirect effects of each variables. The result of the study states that the direct and indirect effect between the cartel, ticket rates, and business competition variables are equally significant. This could be seen from the result of the hypothesis analysis which state that the coefficient is above 0.300. It means that the influence is very strong. From some previous research of monopoly and price, it was found that monopolies in the aviation industry are often unavoidable because they protect airlines from losses. The result also shows that several customers in different levels do not matter about ticket price. For this type of passengers, they only need the route and flight schedule.